How effective is the virtual primary healthcare centers? An experience from rural India - Siddharth Angrish; Meghna Sharma; Md Abu Bashar; Shailesh Tripathi; Md Mahbub Hossain; Sudip Bhattacharya; Amarjeet Singh (Journal of Family Medicine and Primary Care, 2020)
Introduction: Virtual clinic is a new concept in India. This summary describes that how a virtual clinic is transforming the healthcare scenario in rural India. Virtual clinic is based on a social business model, which may involve diverse stakeholders to promote primary care. Aim: This virtual e-clinic aims to expand health outreach in rural and hard-to-reach areas of India and provide primary health care services by connecting local practitioners and health workers visiting patients with qualified allopathic doctors in city through video conferencing technologies. Methodology: This was a cross-sectional study evaluating the feasibility and acceptance of virtual primary care. A convenient sampling method was used. Data on demographic profiles, morbidity patterns, and referrals were collected with proper consent. This virtual clinic comprises of smartphones, monitors, and assistive devices so that patient can interact with the doctors through video-conferencing and can have authenticated prescriptions with standardized protocols. The private organization who initiated the virtual care program had two centers at the beginning and gradually expanded them to 20 in Uttar Pradesh. Consultations charges were kept minimum to no-profit, no-loss. Data were collected from January 2019 to June 2010. Results: Total number of consultations made was 800. Out of 800 patients, 157 patients belonged to age group of ≥60 years. Mean age the patient was 56 ± 1.56 years, among them 421 (52.62%) were male. The participants actively engaged in clinical interactions and completed full sessions of consultations, which highlight the acceptability of the virtual care system and feasibility of effective patient-provider communication and service delivery using digital technologies. Conclusion: The concept of virtual primary care is becoming very popular in rural region where no qualified doctors are available. The initial results of this technological startup appears to be promising; however, it is necessary to evaluate the quality of care, health outcomes, potentials to integrate such innovations in existing primary care, and the legal as well as ethical issues in the future research.